2008
DOI: 10.1002/cncr.23258
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative methylation-specific PCR for the detection of aberrant DNA methylation in liquid-based Pap tests

Abstract: BACKGROUND-Aberrant promoter methylation of selective tumor suppressor genes has been detected in squamous intraepithelial lesions (SIL) and invasive cervical cancer. Identification of methylation profiles of genes that can distinguish high-grade SIL (HSIL) from low-grade SIL (LSIL), and cytologically negative for intraepithelial lesion or malignancy (NILM) residual liquid-based Papanicolaou (Pap) tests may be potentially useful as an ancillary test for cervical cancer screening. METHODS-Using real-time quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…In previous studies DAPK promoter hypermethylation was observed in 2% of normal, 17-55% of HGSILs samples and 45-100% of cancer cases (21,(34)(35)(36)(39)(40)(41)(42)(45)(46)(47)(48). In the present study DAPK promoter hypermethylation was detected in 66.7% of premalignant lesions, percentage which is higher than in previous reports (34)(35)(36) and it was able to distinguish early from late stages of cervical oncogenesis progression. DAPK promoter methylation status seemed to be the best cervical oncogenesis quantitative and qualitative marker, as it was the only marker that was negative in normal tissues.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In previous studies DAPK promoter hypermethylation was observed in 2% of normal, 17-55% of HGSILs samples and 45-100% of cancer cases (21,(34)(35)(36)(39)(40)(41)(42)(45)(46)(47)(48). In the present study DAPK promoter hypermethylation was detected in 66.7% of premalignant lesions, percentage which is higher than in previous reports (34)(35)(36) and it was able to distinguish early from late stages of cervical oncogenesis progression. DAPK promoter methylation status seemed to be the best cervical oncogenesis quantitative and qualitative marker, as it was the only marker that was negative in normal tissues.…”
Section: Discussionmentioning
confidence: 84%
“…Loss of DAPK expression has been shown to occur in a number of malignancies including cervical cancer by enhancing the metastatic potential of cancer cells (40)(41)(42)(43)(44). In previous studies DAPK promoter hypermethylation was observed in 2% of normal, 17-55% of HGSILs samples and 45-100% of cancer cases (21,(34)(35)(36)(39)(40)(41)(42)(45)(46)(47)(48). In the present study DAPK promoter hypermethylation was detected in 66.7% of premalignant lesions, percentage which is higher than in previous reports (34)(35)(36) and it was able to distinguish early from late stages of cervical oncogenesis progression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, the hypermethylation of DAPK promoter was detectable in liquid-based Pap test sample by MSP method. The advantage of using Pap test samples is one kind of noninvasive samples, contains exfoliating cells from the transformation zone of the cervix; thus, the presence of DNA in exfoliating cells has offered an opportunity to find out the predictive and diagnosis biomarkers for CC [27][28][29]. In addition, MSP method is the simple, rapid and inexpensive method that determine the methylation status of CpG islands.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, stromal SPARC inhibits angiogenesis and limits tumor growth in ovarian cancer and glioblastoma (Said and Motamed, 2005;Chlenski et al, 2006Chlenski et al, , 2007Said et al, 2007a, b). Although stromal SPARC was correlated with poor prognosis in pancreatic and small cell lung cancer (Podhajcer et al, 2008), tumor cell SPARC expression was lost due to promoter hypermethylation in pancreatic (Sato et al, 2003), non-small cell lung (Suzuki et al, 2005;Pan et al, 2008), colon (Tai et al, 2005;Yang et al, 2007;Cheetham et al, 2008), cervical (Sova et al, 2006;Kahn et al, 2008), endometrial (Rodriguez-Jimenez et al, 2007) and ovarian cancers (Socha et al, 2009). Stromal SPARC may promote immune/inflammatory cell recruitment in the juxtatumoral stroma (Sangaletti et al, 2003), but may also exert an antiinflammatory role (Said et al, 2007b;Pan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%